A clinicopathologic study of intussusception in Nepalese adults - Shakya, Vikal Chandra; Byanjankar, Bikram; Pandit, Rabin; Shrestha, Anir Ram Moh; Karki, Saurav; Pangeni, Anang (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Intussusception is rate in adults and is usually secondary to a definable pathology. This study was designed to review adult intussusception, including presentation, diagnosis, and pathology.Methods: A retrospective study of 18 cases of intussusception in individuals older than 18 years of age visiting the department of surgery of Civil Service Hospital from 2010 to 2018 was done.Results: There were 18 cases of adult intussusception. The mean age was 49.2 years (range 19-84 years). Abdominal pain and vomiting were the commonest symptoms. The median duration of presentation was 5 days (range 20 hours to 10 months). Three patients (16.6%) presented with generalized peritonitis. There were eight ileocolic, seven ileoileal, and three colocolic intussusceptions. Two patients (11.1%) settled spontaneously. Twelve out of the 18 patients (66.6%) had leading lesions. Benign pathologies were seen in seven cases (38.8%) and malignant in five patients (27.7%). All malignancies were in the large bowlConclusions: Adult intussusception is a rare entity, nearly one-third of their causes are malignant. Surgery is the best recommended treatment, with or without a primary reduction of the intussusception; the latter can result in more limited bowel resection.